In-plane resistivity in graphite intercalation compounds obtained from conduction-electron-spin-resonance measurements - Walmsley, L. [UNESP] (American Physical Society (APS), 1992)
We developed a procedure to take advantage of the magnetic-field- modulation-frequency effect on the line shape of conduction-electron-spin resonance of graphite intercalation compounds (GICs) to extract the absolute value of the in-plane resistivity. We calculated the power absorbed in each slice of the sample normal to the wave penetration, multiplied by a factor to account for the magnetic-field-modulation-frequency effect. Room-temperature spectra of stage-1 AlCl3-intercalated GIC in both H0c and H0c configurations were fitted to the theoretical line shapes and the value of in-plane resistivity (and also the value of c-axis resistivity) obtained from the fitting parameters are in reasonable agreement with those from the literature. © 1992 The American Physical Society.